P-n type Bi2O3 / BNNS heterojunction and preparation method and application thereof

By preparing the P-N-type BI2O3/BNNNS heterogeneous knot, the lack of BN materials in the optical catalytic and adsorption activity was solved, and the high-efficiency degradation of tetracycline antibiotics was achieved, and the degradation rate reached more than 90%.

CN119327502APending Publication Date: 2025-01-21HUANGHUAI UNIV

Patent Information

Application Number
CN202411452500.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

BN materials perform poorly in photocatalytic and adsorption activity, resulting in low efficiency in the treatment of antibiotic contaminants.

Method used

The preparation method of P-N-type BI2O3/BNNNS heterogeneous knot is used to prepare BNNS through the high temperature thermal solution method of boric acid and urea, and use the solvents thermal method to grow BI2O3 nanometer on the surface of the BNNS to form a BI2O3/BNNS composite material.

Benefits of technology

The composite surface area and pore volume of the composite materials are improved, its adsorption and photocatalytic activity is enhanced, and the efficient degradation of tetracycline antibiotics is achieved, and the degradation rate reaches more than 90%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327502A_ABST
    Figure CN119327502A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation of composite photocatalytic materials, discloses a p-n type Bi2O3 / BNNS heterojunction as well as a preparation method and application thereof, and aims at solving the technical problem that a BN material is relatively poor in adsorption and photocatalytic activity. The preparation method comprises the following steps: preparing porous boron nitride nanosheets by taking H3BO3 and CO (NH2) 2 as raw materials through a high-temperature pyrolysis method, and growing Bi2O3 nanowires on the surfaces in situ by utilizing a solvothermal method to obtain the Bi2O3 / BNNS composite material. Wherein BNNS is used as a growth matrix of the Bi2O3 nanowires and can effectively regulate and control growth and agglomeration of the Bi2O3 nanowires, so that the composite material has relatively large specific surface area and pore volume; meanwhile, the BNNS has the characteristics of an n-type semiconductor, and the formation of a p-n junction and a built-in electric field between the Bi2O3 and the BNNS is beneficial to the separation of photo-induced electrons and holes in the catalyst, so that the composite material has higher photocatalytic activity. The composite material is stable in photocatalytic performance, the preparation method is simple, and the composite material has a good application prospect in the aspect of tetracycline analogue degradation under visible light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of composite photocatalytic material preparation, and in particular to a pn-type Bi2O3 / BNNS heterojunction and a preparation method and application thereof. Background Art

[0002] Tetracycline (TC) is one of the most widely used antibiotics in the world and is widely used in agriculture and animal husbandry. However, the decomposition and absorption rate of TC by humans or animals is only 20-30%. A large amount of undecomposed TC will be discharged into the natural environment through various channels, increasing the drug resistance of pathogens and ultimately posing a potential risk to the stability of the ecosystem.

[129] . Photocatalytic technology can use sunlight to effectively decompose antibiotics into water, carbon dioxide and other small molecules. However, this technology has problems such as low efficiency in practical applications, which makes it impossible to apply it on a large scale commercially. Adsorption is another safe and simple method for treating antibiotics, while taking into account the advantages of high efficiency. However, this method can only transfer antibiotics from the water body to the surface of the adsorbent and cannot completely eliminate the hazards of antibiotics. It also has certain limitations in practical applications. In order to overcome the above difficulties, the concept of adsorption-photocatalytic synergy was proposed, and the design of multifunctional materials with both high adsorption and excellent photocatalytic ability has become one of the directions for achieving efficient removal of tetracycline pollutants.

[0003] Studies have shown that highly crystalline two-dimensional BN can effectively inhibit the agglomeration of surface nanoparticles, increase the transfer rate of photogenerated carriers in semiconductor materials, and promote the polarization of tetracycline molecules. It is a highly potential non-metallic co-catalyst. However, the band gap of BN is large and the surface is flat, so the photocatalytic activity is weak, and the adsorption capacity of reactants is limited. In response to this problem, researchers have proposed a variety of modification schemes. Among them, constructing a heterojunction structure is considered to be one of the ideal modification methods, which can make full use of the synergistic effect between different materials to achieve the purpose of improving performance. So far, metal oxide semiconductors (WO3 and bismuth-based semiconductor materials Bi2MoO6, BiVO4, Bi2O3, Bi2O2CO3, etc.) have shown obvious advantages in the field of photocatalytic degradation. For example, in order to improve the photocatalytic activity of BN nanosheets, the invention with publication number CN104888835A discloses a method for preparing a BN / WO3 composite photocatalytic material. Even if the composite photocatalytic material prepared forms a heterojunction, its photocatalytic activity is relatively low, only 82%. Bismuth-based semiconductor materials are considered to be an ideal photocatalyst because of their narrow band gap, low toxicity and relatively low cost. For example, the invention with publication number CN116890099A discloses a photocatalytic material for deep treatment of antibiotics in landfill leachate, which is prepared by compounding BN nanosheets, nanorod-shaped Bi2O3 and nanospherical Co3O4 into a heterojunction to improve the photocatalytic efficiency. However, the use of Co3O4 in this process will increase the cost of use; in addition, if Co3O4 is not added, the photocatalytic degradation efficiency of the BN / Bi2O3 material prepared by simple blending is only 46% (Comparative Example 3). Therefore, proposing a simple and effective preparation method is of great significance for improving the photocatalytic effect of BN materials. Summary of the invention

[0004] In view of the technical problems of poor adsorption and photocatalytic activity of BN materials, the present invention proposes a pn-type Bi2O3 / BNNS heterojunction and a preparation method and application thereof.

[0005] To achieve the above object, the technical solution of the present invention is implemented as follows:

[0006] A method for preparing a pn-type Bi2O3 / BNNS heterojunction, the steps are as follows:

[0007] (1) Adding boric acid and urea to pure water, heating the mixture until the water evaporates, and then calcining I to obtain BNNS;

[0008] (2) adding bismuth nitrate pentahydrate to an N,N-dimethylformamide solution containing BNNS, and adding terephthalic acid to obtain a mixed solution I; subjecting the mixed solution I to a solvothermal reaction, and washing, drying, and calcining the obtained precipitate to obtain a pn-type Bi2O3 / BNNS heterojunction.

[0009] The molar ratio of boric acid to urea in the above step (1) is 1:(6-48).

[0010] Calcination I in the above step (1) refers to calcination at 900-1100° C. for 2-4 hours in nitrogen.

[0011] The mass ratio of bismuth nitrate pentahydrate, BNNS and terephthalic acid in the mixed solution I of the above step (2) is 1:(1.12-4.32):(0.06-0.35).

[0012] The temperature of the solvent thermal reaction in the above step (2) is 120-180° C. and the time is 9-15 hours.

[0013] In the above step (2), the temperature of calcining II is 180-220°C and the time is 2-6h.

[0014] A pn-type Bi2O3 / BNNS heterojunction was prepared using the above-mentioned preparation method.

[0015] The above-mentioned pn-type Bi2O3 / BNNS heterojunction is applied in photocatalytic degradation of antibiotics.

[0016] Furthermore, the above-mentioned antibiotic is tetracycline (TC), oxytetracycline hydrochloride (OTC) or doxycycline hydrochloride (DC).

[0017] Furthermore, the above-mentioned photocatalytic degradation of antibiotics comprises the steps of adding a pn-type Bi2O3 / BNNS heterojunction into a solution containing antibiotics, first adsorbing it in a dark environment, and then placing it under a 300-420nm wavelength, 300W xenon lamp for photocatalytic degradation.

[0018] The beneficial effects produced by the present invention are:

[0019] (1) The present invention uses H3BO3 and CO(NH2)2 as raw materials to prepare porous boron nitride nanosheets (BNNS) with a graphene-like structure by high-temperature pyrolysis, and uses a solvothermal method to in-situ grow Bi2O3 nanowires on the surface to obtain a Bi2O3 / BNNS composite material. BNNS, as the growth matrix of Bi2O3 nanowires, can effectively regulate their growth and agglomeration, making the composite material have a large specific surface area (the specific surface area of ​​Bi2O3 / BNNS-3 can reach 202.586m 2 g -1) and pore volume (the cumulative pore volume of Bi2O3 / BNNS-3 (0.404 cm 3 g -1 ), the high pore volume and large specific surface area make the composite material have more adsorption and reaction active sites, which is conducive to the photocatalytic reaction.

[0020] (2) The Bi2O3 / BNNS prepared in the present invention is a pn-type heterojunction, wherein BNNS has n-type semiconductor characteristics. The formation of the pn junction and the built-in electric field between Bi2O3 and BNNS is beneficial to the separation of photogenerated electrons and holes inside the catalyst, thereby making the composite material have a higher photocatalytic activity.

[0021] (3) The pn-type Bi2O3 / BNNS heterojunction prepared by the present invention has good photocatalytic degradation ability for tetracycline antibiotics. BNNS shows good adsorption capacity and weak photocatalytic activity, while the adsorption capacity and photocatalytic degradation ability of the Bi2O3 / BNNS composite material are better than those of Bi2O3 and BNNS. In addition, the concentration of Bi2O3 / BNNS-3 with the best performance is 50mgL -1 The degradation rates of TC, OTC and DC solutions were all above 90%, and the degradation effect was not affected by other impurity ions (NO3 - , Cl - 、SO4 2- 、Na + , Ca 2+ Mg 2+ and Fe 3+ )’s impact. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 XRD patterns of Bi2O3, BNNS and Bi2O3 / BNNS composite materials prepared in the present invention.

[0024] Figure 2 XPS spectra of Bi2O3 prepared in Comparative Example 1, BNNS prepared in Comparative Example 2 and Bi2O3 / BNNS composite material prepared in Example 3 of the present invention; wherein (a) is the full XPS spectrum; (b) Bi 4f, (c) C 1s, (d) B 1s, (e) N 1s and (f) O 1s high-resolution XPS spectra.

[0025] Figure 3 FT-IR spectra of Bi2O3 prepared in Comparative Example 1, BNNS prepared in Comparative Example 2 and Bi2O3 / BNNS-3 prepared in Example 3 of the present invention.

[0026] Figure 4 SEM and TEM images of Bi2O3 (Comparative Example 1), BNNS (Comparative Example 2) and Bi2O3 / BNNS-3 prepared in the present invention; among them, (a) SEM and (d) TEM images of Bi2O3; (b) SEM and (e) TEM images of BNNS; (c) SEM, (f) TEM, (g) HRTEM, (h) HAADF and (im) element distribution diagram of Bi2O3 / BNNS composite material.

[0027] Figure 5 The specific surface areas and pore size analysis diagrams of Bi2O3 (Comparative Example 1), BNNS (Comparative Example 2) and Bi2O3 / BNNS-3 prepared in the present invention, wherein (a) is the N2 adsorption-desorption isotherm; (b) is the pore size distribution curve; (c) is the cumulative pore volume curve and (d) is the specific surface area / cumulative pore volume diagram.

[0028] Figure 6 Visible light absorption performance diagram of Bi2O3 (Comparative Example 1), BNNS (Comparative Example 2) prepared in the present invention and Bi2O3 / BNNS prepared in Examples 1-5; wherein (a) is the UV-visible absorption spectrum; and (b) is the bandgap width of BNNS and Bi2O3.

[0029] Figure 7 (ab) Mott-Schottky curves and (cd) VB-XPS spectra of Bi2O3 (Comparative Example 1) and BNNS (Comparative Example 2) of the present invention.

[0030] Figure 8 Schematic diagram of the energy band structure of Bi2O3 (Comparative Example 1), BNNS (Comparative Example 2) and Bi2O3 / BNNS-3 prepared in the present invention.

[0031] Fig. 9 TRPL spectra of Bi2O3 prepared in the present invention (Comparative Example 1) and Bi2O3 / BNNS composite materials prepared in Examples 1-5.

[0032] Fig.10 Electrochemical properties of Bi2O3 (Comparative Example 1), BNNS (Comparative Example 2) prepared in the present invention and Bi2O3 / BNNS composite materials prepared in Examples 1-5; wherein (a) is a transient photocurrent curve; and (b) is an electrochemical impedance curve.

[0033] Fig.11 Photocatalytic degradation performance of tetracycline by Bi2O3 (Comparative Example 1), BNNS (Comparative Example 2) prepared by the present invention and Bi2O3 / BNNS composite materials prepared in Examples 1-5; wherein (a) is the photocatalytic degradation curve; (b) is the first-order kinetic model fitting curve; and (c) is the rate constant.

[0034] Fig.12 TC curves of photocatalytic degradation after adding different scavengers to the Bi2O3 / BNNS-3 composite material prepared in Example 3 of the present invention.

[0035] Fig.13 The cyclic performance of the Bi2O3 / BNNS-3 composite material prepared in Example 3 of the present invention for photocatalytic degradation of TC; wherein, (a) is the 5-cycle degradation curve of Bi2O3 / BNNS-3 on TC solution; XRD (b) and FT-IR spectra (c) of Bi2O3 / BNNS-3 before and after the cycle.

[0036] Fig.14 The photocatalytic degradation process of TC molecules; where (a) is the UV-visible absorption spectrum of TC solution during the photocatalytic degradation process; (b) is the liquid phase mass spectrum of the solution after 20 minutes of illumination; (c) is the liquid phase mass spectrum of TC solution and the solution after 120 minutes of illumination; (d) is the inferred photocatalytic degradation process of TC molecules.

[0037] Fig.15 The Bi2O3 / BNNS-3 composite material prepared in Example 3 of the present invention has a broad spectrum of photocatalytic activity on organic matter; wherein, (a) is the TC degradation curve of Bi2O3 / BNNS-3 in an environment where inorganic salt ions coexist; (b) is the degradation curve of Bi2O3 / BNNS-3 for TC, OTC and DC.

[0038] Fig.16 This is the photocatalytic degradation mechanism of TC by Bi2O3 / BNNS composite materials. DETAILED DESCRIPTION

[0039] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Example 1

[0041] The preparation method of the pn-type Bi2O3 / BNNS heterojunction of this embodiment comprises the following steps:

[0042] (1) Preparation of BNNS: BNNS was prepared by a two-step method. First, boric acid (H3BO3) and urea (CO(NH2)2) (the molar ratio of H3BO3 to CO(NH2)2 was 1:48) were weighed and dispersed in a beaker containing 200 mL of pure water. Then, the mixture was heated and stirred in a 70°C water bath until the water in the beaker was completely evaporated to obtain a white powdery precursor. Finally, the precursor was calcined at 1100°C in nitrogen for 4 h to obtain white BNNS.

[0043] (2) Preparation of Bi2O3 / BNNS composite material: 0.5mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) was dispersed in 50mL of C3H7NO solution containing BNNS (1.0485g) and stirred for 30min, and 0.1mmol of terephthalic acid was added to obtain a mixed solution. The mixed solution was kept at 150℃ for 12h. After cooling to room temperature, the obtained precipitate was washed and dried with N,N-dimethylformamide (C3H7NO) and anhydrous ethanol to obtain a precursor. Finally, a pn-type Bi2O3 / BNNS heterojunction was obtained by calcining in a muffle furnace at 200℃ for 4h, in which the Bi2O3 content was 10wt%, recorded as Bi2O3 / BNNS-1.

[0044] Example 2

[0045] The preparation method of the pn-type Bi2O3 / BNNS heterojunction of this embodiment comprises the following steps:

[0046] (1) Preparation of BNNS: BNNS was prepared by a two-step method. First, boric acid (H3BO3) and urea (CO(NH2)2) (the molar ratio of H3BO3 to CO(NH2)2 was 1:48) were weighed and dispersed in a beaker containing 200 mL of pure water. Then, the mixture was heated and stirred in a 70°C water bath until the water in the beaker was completely evaporated to obtain a white powdery precursor. Finally, the precursor was calcined at 1100°C in nitrogen for 4 h to obtain white BNNS.

[0047] (2) Preparation of Bi2O3 / BNNS composite material: 0.5mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) was dispersed in 50mL of C3H7NO solution containing BNNS (0.6602g) and stirred for 30min, and 0.1mmol of terephthalic acid was added to obtain a mixed solution. The mixed solution was kept at 150℃ for 12h. After cooling to room temperature, the obtained precipitate was washed and dried with N,N-dimethylformamide (C3H7NO) and anhydrous ethanol to obtain a precursor. Finally, a pn-type Bi2O3 / BNNS heterojunction was obtained by calcining in a muffle furnace at 200℃ for 4h, in which the Bi2O3 content was 15wt%, recorded as Bi2O3 / BNNS-2.

[0048] Example 3

[0049] The preparation method of the pn-type Bi2O3 / BNNS heterojunction of this embodiment comprises the following steps:

[0050] (1) Preparation of BNNS: BNNS was prepared by a two-step method. First, boric acid (H3BO3) and urea (CO(NH2)2) (the molar ratio of H3BO3 to CO(NH2)2 was 1:48) were weighed and dispersed in a beaker containing 200 mL of pure water. Then, the mixture was heated and stirred in a 70°C water bath until the water in the beaker was completely evaporated to obtain a white powdery precursor. Finally, the precursor was calcined at 1100°C in nitrogen for 4 h to obtain white BNNS.

[0051] (2) Preparation of Bi2O3 / BNNS composite material: 0.5mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) was dispersed in 50mL of C3H7NO solution containing BNNS (0.4660g) and stirred for 30min, and 0.1mmol of terephthalic acid was added to obtain a mixed solution. The mixed solution was kept at 150℃ for 12h. After cooling to room temperature, the obtained precipitate was washed and dried with N,N-dimethylformamide (C3H7NO) and anhydrous ethanol to obtain a precursor. Finally, a pn-type Bi2O3 / BNNS heterojunction was obtained by calcining in a muffle furnace at 200℃ for 4h, in which the Bi2O3 content was 20wt%, recorded as Bi2O3 / BNNS-3.

[0052] Example 4

[0053] The preparation method of the pn-type Bi2O3 / BNNS heterojunction of this embodiment comprises the following steps:

[0054] (1) Preparation of BNNS: BNNS was prepared by a two-step method. First, boric acid (H3BO3) and urea (CO(NH2)2) (the molar ratio of H3BO3 to CO(NH2)2 was 1:48) were weighed and dispersed in a beaker containing 200 mL of pure water. Then, the mixture was heated and stirred in a 70°C water bath until the water in the beaker was completely evaporated to obtain a white powdery precursor. Finally, the precursor was calcined at 1100°C in nitrogen for 4 h to obtain white BNNS.

[0055] (2) Preparation of Bi2O3 / BNNS composite material: 0.5mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) was dispersed in 50mL of C3H7NO solution containing BNNS (0.3495g) and stirred for 30min, and 0.1mmol of terephthalic acid was added to obtain a mixed solution. The mixed solution was kept at 150℃ for 12h. After cooling to room temperature, the obtained precipitate was washed and dried with N,N-dimethylformamide (C3H7NO) and anhydrous ethanol to obtain a precursor. Finally, a pn-type Bi2O3 / BNNS heterojunction was obtained by calcination in a muffle furnace at 200℃ for 4h, in which the Bi2O3 content was 25wt%, recorded as Bi2O3 / BNNS-4.

[0056] Example 5

[0057] The preparation method of the pn-type Bi2O3 / BNNS heterojunction of this embodiment comprises the following steps:

[0058] (1) Preparation of BNNS: BNNS was prepared by a two-step method. First, boric acid (H3BO3) and urea (CO(NH2)2) (the molar ratio of H3BO3 to CO(NH2)2 was 1:48) were weighed and dispersed in a beaker containing 200 mL of pure water. Then, the mixture was heated and stirred in a 70°C water bath until the water in the beaker was completely evaporated to obtain a white powdery precursor. Finally, the precursor was calcined at 1100°C in nitrogen for 4 h to obtain white BNNS.

[0059] (2) Preparation of Bi2O3 / BNNS composite material: 0.5mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) was dispersed in 50mL of C3H7NO solution containing BNNS (0.2718g) and stirred for 30min, and 0.1mmol of terephthalic acid was added to obtain a mixed solution. The mixed solution was kept at 150℃ for 12h. After cooling to room temperature, the obtained precipitate was washed and dried with N,N-dimethylformamide (C3H7NO) and anhydrous ethanol to obtain a precursor. Finally, a pn-type Bi2O3 / BNNS heterojunction was obtained by calcining in a muffle furnace at 200℃ for 4h, in which the Bi2O3 content was 30wt%, recorded as Bi2O3 / BNNS-5.

[0060] Example 6

[0061] The preparation method of the pn-type Bi2O3 / BNNS heterojunction of this embodiment comprises the following steps:

[0062] (1) Preparation of BNNS: BNNS was prepared by a two-step method. First, boric acid (H3BO3) and urea (CO(NH2)2) (the molar ratio of H3BO3 and CO(NH2)2 was 1:6) were weighed and dispersed in a beaker containing 200 mL of pure water. Then, the mixture was heated and stirred in a 70°C water bath until the water in the beaker was completely evaporated to obtain a white powdery precursor. Finally, the precursor was calcined at 900°C in nitrogen for 4 h to obtain white BNNS.

[0063] (2) Preparation of Bi2O3 / BNNS composite material: 0.5 mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) was dispersed in 50 mL of C3H7NO solution containing BNNS (0.4660 g) and stirred for 30 min. 0.3 mmol of terephthalic acid was added to obtain a mixed solution. The mixed solution was kept at 120°C for 15 h. After cooling to room temperature, the obtained precipitate was washed and dried with N,N-dimethylformamide (C3H7NO) and anhydrous ethanol to obtain a precursor. Finally, a pn-type Bi2O3 / BNNS heterojunction was obtained by calcining in a muffle furnace at 180°C for 6 h, in which the Bi2O3 content was 20 wt%, recorded as Bi2O3 / BNNS-3-1.

[0064] Example 7

[0065] The preparation method of the pn-type Bi2O3 / BNNS heterojunction of this embodiment comprises the following steps:

[0066] (1) Preparation of BNNS: BNNS was prepared by a two-step method. First, boric acid (H3BO3) and urea (CO(NH2)2) (the molar ratio of H3BO3 and CO(NH2)2 was 1:15) were weighed and dispersed in a beaker containing 200 mL of pure water. Then, the mixture was heated and stirred in a 70°C water bath until the water in the beaker was completely evaporated to obtain a white powdery precursor. Finally, the precursor was calcined at 1100°C in nitrogen for 2 h to obtain white BNNS.

[0067] (2) Preparation of Bi2O3 / BNNS composite material: 0.5mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) was dispersed in 50mL of C3H7NO solution containing BNNS (0.3495g) and stirred for 30min, and 0.5mmol of terephthalic acid was added to obtain a mixed solution. The mixed solution was kept at 180℃ for 9h. After cooling to room temperature, the obtained precipitate was washed and dried with N,N-dimethylformamide (C3H7NO) and anhydrous ethanol to obtain a precursor. Finally, a pn-type Bi2O3 / BNNS heterojunction was obtained by calcining in a muffle furnace at 190℃ for 5h, in which the Bi2O3 content was 25wt%, recorded as Bi2O3 / BNNS-4-1.

[0068] Example 8

[0069] The preparation method of the pn-type Bi2O3 / BNNS heterojunction of this embodiment comprises the following steps:

[0070] (1) Preparation of BNNS: BNNS was prepared by a two-step method. First, boric acid (H3BO3) and urea (CO(NH2)2) (the molar ratio of H3BO3 to CO(NH2)2 was 1:24) were weighed and dispersed in a beaker containing 200 mL of pure water. Then, the mixture was heated and stirred in a 70°C water bath until the water in the beaker was completely evaporated to obtain a white powdery precursor. Finally, the precursor was calcined at 1000°C in nitrogen for 3 h to obtain white BNNS.

[0071] (2) Preparation of Bi2O3 / BNNS composite material: 0.5mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) was dispersed in 50mL of C3H7NO solution containing BNNS (0.4660g) and stirred for 30min, and 0.4mmol of terephthalic acid was added to obtain a mixed solution. The mixed solution was kept at 140℃ for 14h. After cooling to room temperature, the obtained precipitate was washed and dried with N,N-dimethylformamide (C3H7NO) and anhydrous ethanol to obtain a precursor. Finally, a pn-type Bi2O3 / BNNS heterojunction was obtained by calcining in a muffle furnace at 210℃ for 3h, in which the Bi2O3 content was 20wt%, recorded as Bi2O3 / BNNS-3-2.

[0072] Example 9

[0073] The preparation method of the pn-type Bi2O3 / BNNS heterojunction of this embodiment comprises the following steps:

[0074] (1) Preparation of BNNS: BNNS was prepared by a two-step method. First, boric acid (H3BO3) and urea (CO(NH2)2) (the molar ratio of H3BO3 and CO(NH2)2 was 1:36) were weighed and dispersed in a beaker containing 200 mL of pure water. Then, the mixture was heated and stirred in a 70°C water bath until the water in the beaker was completely evaporated to obtain a white powdery precursor. Finally, the precursor was calcined at 1000°C in nitrogen for 4 h to obtain white BNNS.

[0075] (2) Preparation of Bi2O3 / BNNS composite material: 0.5mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) was dispersed in 50mL of C3H7NO solution containing BNNS (0.6602g) and stirred for 30min, and 0.2mmol of terephthalic acid was added to obtain a mixed solution. The mixed solution was kept at 160℃ for 11h. After cooling to room temperature, the obtained precipitate was washed and dried with N,N-dimethylformamide (C3H7NO) and anhydrous ethanol to obtain a precursor. Finally, a pn-type Bi2O3 / BNNS heterojunction was obtained by calcining in a muffle furnace at 220℃ for 2h, in which the Bi2O3 content was 15wt%, recorded as Bi2O3 / BNNS-2-1.

[0076] Comparative Example 1

[0077] The preparation method of Bi2O3 nanowires in this comparative example comprises the following steps:

[0078] Weigh 0.5 mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) and disperse it in 50 mL of N,N-dimethylformamide.

[0079] (C3H7NO) solution and stirred for 30 min. 0.1 mmol of terephthalic acid (C8H6O4) was added to the above solution and stirred for 30 min. Then, the mixed solution was kept at 150 ° C for 12 h. After cooling to room temperature, the obtained precipitate was washed and dried with C3H7NO and anhydrous ethanol to obtain a precursor. Finally, Bi2O3 nanowires were obtained by calcining in a muffle furnace at 200 ° C for 4 h.

[0080] Comparative Example 2

[0081] The preparation method of BNNS in this comparative example comprises the following steps:

[0082] BNNS was prepared by a two-step method. First, boric acid (H3BO3) and urea (CO(NH2)2) (the molar ratio of H3BO3 and CO(NH2)2 was 1:48) were weighed and dispersed in a beaker containing 200 mL of pure water. Then, the mixture was heated and stirred in a 70°C water bath until the water in the beaker was completely evaporated to obtain a white powder precursor. Finally, the precursor was calcined at 1100°C in nitrogen for 4 h to obtain white BNNS.

[0083] Implementation effect example

[0084] The pn-type Bi2O3 / BNNS heterojunctions prepared in Examples 1-5, the Bi2O3 nanowires prepared in Comparative Example 1, and the BNNS prepared in Comparative Example 2 were analyzed for crystal structure, chemical composition, micromorphology, and photoelectrochemical performance. The specific results are as follows.

[0085] (1) Crystal structure analysis

[0086] The crystal structure and composition of the prepared Bi2O3 nanowires, BNNS and composite materials were investigated by XRD. Figure 1 As shown. It can be seen from the figure that the Bi2O3 nanowires prepared by the present invention have diffraction peaks at 2θ=28.0°, 30.8°, 31.8°, 32.8°, 46.3°, 54.5° and 55.6°, which correspond to the (201), (211), (002), (222), (400), (203) and (421) crystal planes of β-Bi2O3 (JCPDS No.27-0050), respectively. For BNNS, it can be clearly observed that there are diffraction peaks belonging to the h-BN (JCPDS No.34-0421) (002) and (100) crystal planes at 25.8° and 42.5°. And the X-ray diffraction peak of BNNS is relatively wide, indicating that there are many defective structures inside it, which greatly reduces the crystallinity of BNNS. In addition, the shift of the diffraction peak position proves that BNNS contains doping of impurity elements (O and C, etc.). The presence of characteristic diffraction peaks of Bi2O3 and BNNS can be clearly seen in the XRD spectrum of the Bi2O3 / BNNS composite material, and the intensity of the corresponding diffraction peak of Bi2O3 also increases with the increase of its content, which indicates that the composite material has been successfully prepared. In addition, the half-peak width of the diffraction peak of Bi2O3 in the composite material is narrower than that of Bi2O3, indicating that BNNS can effectively improve the crystallinity of Bi2O3 as the growth matrix of Bi2O3. In addition, the strong interaction between Bi2O3 and BNNS causes a slight shift in the diffraction peak of BNNS.

[0087] (2) Chemical composition analysis

[0088] In order to deeply analyze the surface element composition and chemical state of Bi2O3, BNNS and Bi2O3 / BNNS composite materials, the XPS spectra of the three samples were tested and analyzed, and the binding energy of each element was corrected by C1s (284.8eV). Figure 2 Figure a) shows that the surface of the composite material contains five elements: Bi, O, C, B and N, and no other impurity elements appear. Figure 2 Figure b is the high-resolution XPS spectra of Bi2O3 and Bi2O3 / BNNS-3 for Bi 4f, in which the two characteristic peaks belong to Bi 4f 5 / 2 and Bi 4f 7 / 2 , and the energy level difference between the two characteristic peaks of these two materials is 5.3eV. The difference is that the Bi 4f 5 / 2 and Bi 4f 7 / 2The binding energies are relatively large, at 164.4 and 159.1 eV, respectively, while the Bi 4f 5 / 2 and Bi 4f 7 / 2 The binding energies of Bi2O3 and BNNS-3 / BNNS-3 are 164.2 and 158.9 eV. Figure 2 Figure c) can be fitted into three characteristic peaks, among which the peak at 284.8 eV belongs to the CC bond of the impurity carbon source. The characteristic peaks at 288.3 and 285.8 eV in Bi2O3 correspond to the CO bond and Bi-C bond, respectively, indicating that a small amount of C element was introduced into Bi2O3 during the preparation process. Similarly, the binding energy of the CO bond and Bi-C bond in Bi2O3 / BNNS-3 (288.1 and 285.6 eV) is smaller than that in Bi2O3. B1s and N1s high-resolution XPS spectra of BNNS and Bi2O3 / BNNS-3 ( Figure 2 Figure (middle) shows that the characteristic peaks of BNNS at 192.6, 190.5 and 398.1 eV belong to BO, BN and NB bonds, respectively. However, the binding energies of BO, BN and NB bonds in the composite material (192.8, 190.7 and 398.3 eV) are greater than the corresponding binding energies in BNNS. The O1s high-resolution XPS spectra of Bi2O3, BNNS and Bi2O3 / BNNS-3 were then analyzed. Figure 2 The two fitting peaks in Bi2O3 belong to Bi-O bond (529.9eV) and surface chemically adsorbed oxygen (531.4eV). BNNS has a characteristic peak of BO bond at 532.5eV. Among the three characteristic peaks of the composite material, the binding energy of Bi-O bond (529.7eV) and surface chemically adsorbed oxygen (531.2eV) is lower than that of Bi2O3, while the binding energy of BO bond (532.7eV) is higher than that of BNNS. This phenomenon shows that the strong interaction between Bi2O3 and BNNS in the Bi2O3 / BNNS composite material leads to the transfer of internal electrons.

[0089] The functional groups and chemical bonds of Bi2O3, BNNS and Bi2O3 / BNNS composites were analyzed by FT-IR technology. Figure 3 As shown, Bi2O3, BNNS and Bi2O3 / BNNS-3 are at ~3400cm -1 The broad peak at 2820-3000cm corresponds to the stretching vibration mode of the OH bond on the surface of the material. -1 and 950-1200cm -1 The absorption band of is caused by the vibration of CH bond. This shows that there are a lot of -OH hanging on the surface of the three materials, and a small amount of C element exists inside. In addition, BNNS has a strong absorption band at 3050-3260cm-1 The absorption bands belonging to NH bonds were observed at 425-640cm, indicating that a large number of amino groups were generated on the surface of BNNS during the pyrolysis of the precursor. The hydroxyl and amino groups provided sufficient hydrogen bonding ligands to promote the formation of heterojunctions between BNNS and Bi2O3. -1 and 1285-1580cm -1 The absorption peak belongs to the Bi-O bond in the BiO6 octahedron, 717-909cm -1 The absorption peak at ∼803 and ∼1380 cm-1 is caused by the stretching vibration of Bi-O-Bi. -1 The characteristic absorption peaks at belong to the BNB interlayer bending vibration peak and the intralayer BN bond stretching vibration peak, respectively, which proves the successful synthesis of Bi2O3 / BNNS composite materials and that the addition of BNNS will not affect the chemical structure of Bi2O3.

[0090] (3) Micromorphology analysis

[0091] Figure 4 Figures a-f are the SEM and TEM images of Bi2O3, BNNS and Bi2O3 / BNNS composites, respectively. Figure 4 Figure a shows that Bi2O3 is a one-dimensional fibrous structure with uniform size and high aspect ratio, and there is obvious agglomeration. Slightly different from the SEM observations, the TEM image of Bi2O3 ( Figure 4 Figure d) shows that the length of Bi2O3 is only ~100nm, but the diameter is still ~30nm. Figure 4 Figures b and e are the SEM and TEM images of BNNS, respectively. It can be seen that BNNS presents an ultra-thin graphene-like layered structure with a large number of wrinkles on the surface. This structure gives BNNS a large specific surface area, which can provide sufficient active sites for the nucleation growth of Bi2O3 and the subsequent photocatalytic reaction process. SEM image of Bi2O3 / BNNS composite material ( Figure 4 Figure c) shows that its overall structure is similar to that of BNNS, but a layer of fine "hair" can be seen on the surface of the composite material. TEM image of the composite material ( Figure 4 Figure f) in the middle more intuitively shows that a certain number of nanowires are evenly dispersed on the surface of BNNS. Figure 4 Figure g is a HRTEM image of the composite material, from which the crystal structure of each part of the composite material can be directly observed. There are obvious lattice fringes in both the sheet structure and the nanowire structure. The measurement shows that the spacing between the two fringes is 3.47 and The (002) and (201) crystal planes corresponding to h-BN and β-Bi2O3 respectively prove that the nanowires in the composite material are Bi2O3. The above results show that BNNS as a carrier can regulate the growth of Bi2O3 nanowires, greatly reducing their radius and length. The special "hairy" structure of the Bi2O3 / BNNS composite material not only brings a larger specific surface area, which is beneficial to the adsorption of the catalyst on the reactants, but also effectively improves the utilization rate of the material for light. In addition, the close bonding between BNNS and Bi2O3 also confirms the successful formation of the heterojunction structure. Figure 4 The middle hm figure shows the HAADF and elemental mapping of the Bi2O3 / BNNS composite material, which further proves the uniform distribution of Bi2O3 nanowires on the BNNS surface.

[0092] The surface properties of the catalyst are one of the main factors affecting its photocatalytic activity. The N2 adsorption-desorption isotherms of Bi2O3, BNNS and Bi2O3 / BNNS-3 were tested. Figure 5 As shown in Figure a. The N2 adsorption-desorption curve of Bi2O3 is a type IV isotherm, and there is an H3 type hysteresis loop, indicating that the material is a mesoporous material. BNNS presents a type I isotherm with an H4 type hysteresis loop, proving that there are abundant micropores and slit-shaped mesopores formed by the accumulation of lamellar structures. Unlike the above two materials, the Bi2O3 / BNNS composite material exhibits a typical type IV isotherm and an H4 type hysteresis loop, revealing the hierarchical porous structure of the material. Figure 5 Figure b shows that Bi2O3 / BNNS-3 not only presents a narrow pore size distribution centered at 4nm in the range of 2-8nm, but also has a large number of pores with diameters of 8-80nm. The cumulative pore volume (0.404cm 3 g -1 ) is larger than BNNS(0.175cm 3 g -1 ) and Bi2O3(0.231cm 3 g -1 )( Figure 5 In addition, the specific surface area of ​​Bi2O3 / BNNS-3 (202.586 m 2 g -1 ) close to BNNS(225.889m 2 g -1 ), and is much larger than Bi2O3 (58.162m 2 g -1 )( Figure 5The above results indicate that the Bi2O3 nanowires are evenly dispersed on the surface of BNNS, which allows the composite material to retain the pore size characteristics of BNNS and Bi2O3 materials while generating new stacked pores. In short, the high pore volume and large specific surface area allow the composite material to have more adsorption and reaction active sites, which is conducive to the photocatalytic reaction.

[0093] (4) Photoelectrochemical performance analysis

[0094] The UV-visible absorption spectra of BNNS, Bi2O3 and Bi2O3 / BNNS composites were tested to explore their light utilization efficiency. Figure 6 Figure a shows that Bi2O3 has excellent visible light absorption ability, and its absorption edge is at ~550nm, while BNNS has almost no light absorption ability in the visible light range. However, after the two materials are combined, the light absorption ability of the whole band has been improved. The reason for this phenomenon is that the special microstructure of the Bi2O3 / BNNS composite material is conducive to the reflection of light inside it. Based on the above test data, the Kubelka-Munk formula is used to calculate the bandgap widths of Bi2O3 and BNNS to be 2.32 and 3.36 eV respectively. Figure 6 (b in the middle). Since the raw materials (H3BO3 and CO(NH2)2) used in the preparation of BNNS contain a large number of other elements (C, O and H) in addition to B and N, a small amount of impurity elements will be doped inside BNNS, which will affect the energy level structure of h-BN and make the bandgap of BNNS smaller than that of common h-BN (5-6eV).

[0095] The analysis of the band structures of Bi2O3 and BNNS is helpful to further understand the transfer of photogenerated carriers in Bi2O3 / BNNS composites. Figure 7 Figures a and b in the middle show that the slope of the curve for Bi2O3 is negative, indicating that it is a p-type semiconductor. For BNNS, the corresponding slope of the curve is positive, showing the characteristics of an n-type semiconductor. After calculation, the flat band potential (E fb ) are 0.55 and -0.97 V (relative to Ag / AgCl electrode), respectively. Further calculations show that the E of Bi2O3 and BNNS relative to the standard hydrogen electrode VB and E CB According to the band gap widths of Bi2O3 and BNNS obtained above (2.32 and 3.36 eV), it can be concluded that the E CB and E VB are -1.35 and 2.41 eV.

[0096] In order to verify the accuracy of the above results, the VB-XPB spectra of Bi2O3 and BNNS were tested and analyzed. Figure 7 As shown in Figures c and d. In addition, E VB,NHE The calculation formula is shown in formula (1):

[0097]

[0098] in, is the power function of the instrument used in the VB-XPS test (4.60 eV). The E of Bi2O3 and BNNS was calculated. VB,NHE 0.95 and 2.39 eV respectively, E CB,NHE The band structures of Bi2O3 and BNNS are as follows: Figure 8 As shown on the left, with the formation of the pn junction between Bi2O3 and BNNS, the Fermi level (E F ) will gradually align. Because the E F Close to E VB and E CB , so the energy bands of Bi2O3 and BNNS will move up and down respectively. Due to the existence of pn junction, the e in Bi2O3 - It is easier to transfer to BNNS. + It is easier to transfer to Bi2O3, thereby inhibiting the recombination of photogenerated carriers. In addition, the depletion of holes in the p-type semiconductor leads to a negative surface space charge on the Bi2O3 surface. Similarly, the depletion of electrons in the n-type semiconductor makes the surface charge of BNNS positive. Therefore, a built-in electric field is formed inside the composite material from BNNS to Bi2O3, further enhancing the transfer of holes and electrons between the materials ( Figure 8 right).

[0099] The separation rate of photogenerated charge carriers in a catalyst greatly affects its photocatalytic activity. The recombination dynamics of photoinduced charge carriers in Bi2O3 and Bi2O3 / BNNS composites were studied by time-resolved fluorescence spectroscopy (TRPL). Fig. 9 As shown in the figure, by fitting the test results with a double exponential function, it is found that the carrier lifetime of the composite material is greater than that of Bi2O3 (18.63ns), especially Bi2O3 / BNNS-3 (21.73ns). This phenomenon proves that the formation of the pn junction greatly improves the separation and transportation of photogenerated carriers in the catalyst.

[0100] The electrochemical properties of semiconductor materials can also be used to study the carrier separation efficiency. Fig.10 Figure a shows BNNS, Bi2O3 and Bi2O 3 / The photocurrent response curve of the BNNS composite material shows that the above materials all generate current under light, but the photocurrent density of the composite material is greater than that of BNNS and Bi2O3. In addition, the electrochemical impedance spectroscopy (EIS) curve of semiconductor materials can be used to study the resistance encountered during charge transfer. Test results ( Fig.10 Figure b) shows that the EIS radius of the composite material is smaller than that of BNNS and Bi2O3. In summary, the photoelectrochemical results further prove that Bi2O 3 / The presence of pn junction and built-in electric field inside BNNS composite materials promotes the formation of efficient charge transfer pathways, thus giving it a more excellent carrier separation rate and high charge transfer efficiency.

[0101] Application Examples

[0102] The photocatalytic degradation of tetracycline antibiotics was used as a model to explore the photocatalytic activity of the catalyst. The antibiotics included tetracycline hydrochloride (TC), oxytetracycline hydrochloride (OTC) and doxycycline hydrochloride (DC), with a concentration of 50 mg L -1 The volume of antibiotic solution and the mass of catalyst used in the photocatalytic degradation experiment were 100 mL and 20 mg, respectively. The entire photocatalytic process lasted for 180 min, including 60 min of stirring in a dark environment to reach adsorption equilibrium and 120 min of continuous irradiation with a xenon lamp.

[0103] At a concentration of 50 mg L -1 TC solution was used as a simulated pollutant and a 300W xenon lamp (λ=300-420nm) was used as a light source to test the removal efficiency of BNNS, Bi2O3 and Bi2O3 / BNNS composites on TC molecules, and then their photocatalytic activity was evaluated. Fig.11Figure a shows that the removal rates of TC by BNNS and Bi2O3 are 58.43% and 38.62% respectively, and the removal rates of TC by the composite materials are all above 80%, among which Bi2O3 / BNNS-3 has the best effect (94.65%). In addition, by comparison, it can be found that although Bi2O3 has a poor adsorption capacity for TC, BNNS and composite materials have excellent TC adsorption capacity. In particular, the adsorption amount of TC molecules by the Bi2O3 / BNNS composite material is significantly higher than that of Bi2O3 and BNNS, which confirms that the large specific surface area and high pore volume of the catalyst are conducive to its adsorption and capture of reactants, and proves that the Bi2O3 / BNNS composite material meets the requirements of adsorption-photocatalytic synergy. It is worth noting that BNNS has certain semiconductor properties and therefore exhibits a certain photocatalytic degradation ability. Then, the first 80 minutes with a relatively fast reaction rate was selected as the time interval, and the pseudo-first-order kinetic model was used to evaluate the photocatalytic degradation rate of TC molecules by BNNS, Bi2O3 and Bi2O3 / BNNS composite materials. As shown Fig.11 As shown in Figures b and c, the photocatalytic degradation of TC molecules by all materials conforms to the pseudo-first-order kinetic model. The kinetic constants K of BNNS and Bi2O3 are calculated to be 0.285×10 -2 and 0.372×10 -2 min -1 For Bi2O3 / BNNS composites, due to the formation of pn junction, their kinetic constants are greater than those of BNNS and Bi2O3, among which Bi2O3 / BNNS-3 has the largest kinetic constant (2.177×10 - 2 min -1 ). The photocatalytic activity of BNNS itself is weak, so as the BNNS content further increases, the kinetic constant of the composite material decreases, that is, the photocatalytic activity decreases.

[0104] In order to further explore the active groups in the photocatalytic degradation process of Bi2O3 / BNNS composites, a set of free radical capture experiments were designed using Bi2O3 / BNNS-3 as an example. PBQ, TEOA and IPA were used to capture superoxide radicals (·O2 - ), photogenerated holes (h + ) and hydroxyl radicals (·OH) are captured. Fig.12 As shown in the figure, the addition of TEOA had no significant effect on the photocatalytic degradation of TC, while the addition of PBQ and IPA inhibited the degradation of TC to a certain extent, with the inhibition effects of 54.21% and 39.76%, respectively. -and ·OH play a certain role in the photocatalytic degradation of TC by Bi2O3 / BNNS composites, and ·O2 - Play a key role.

[0105] Considering that the cost of photocatalysts in practical applications mainly depends on the recycling capacity of the material itself, the photocatalytic degradation effect of Bi2O3 / BNNS composite materials on TC was further tested when they were recycled four times. The results showed that ( Fig.13 (a), after four cycles, the photocatalytic degradation effect of Bi2O3 / BNNS-3 can still be maintained at 93.64% of the initial value. The XRD spectrum and FT-IR curve of the photocatalyst after four cycles were further tested and compared with the data before the cycle. Fig.13 Figure b shows that the crystal structure and phase composition of Bi2O3 / BNNS-3 before and after the reaction did not change significantly, and the crystallinity of the sample increased slightly after the reaction, which is speculated to be caused by the hydrolysis of some unstable structures. In addition, the FT-IR results ( Fig.13 Figure c) shows that the strength of OH and CH bonds in Bi2O3 / BNNS-3 increases after recycling. This phenomenon indicates that a small amount of TC molecules or other degradation products are adsorbed on the catalyst surface, but the chemical structure and chemical composition of the catalyst itself have not changed. Therefore, the Bi2O3 / BNNS composite material exhibits excellent structural stability and recyclability.

[0106] Taking Bi2O3 / BNNS-3 as an example, the UV-Vis spectrum of TC solution during the degradation process was tested. Fig.14 As shown in Figure a, after 60 minutes of adsorption, the UV-Vis spectrum intensity of the solution dropped significantly. After photocatalytic degradation, the UV-Vis absorption spectrum of the solution was significantly different from that of the TC solution, indicating that the TC molecule had been decomposed into other molecules. TC molecules contain a large number of double bonds, amine groups, aromatic rings, and phenolic hydroxyl groups, which are easily attacked by active free radicals. Liquid chromatography-mass spectrometry can be used to test and analyze the intermediate components in the photocatalytic degradation process, so as to further study the degradation process of TC molecules. Fig.14 Figure b shows that after 20 minutes of photocatalytic degradation, a large amount of intermediates exist in the liquid. Fig.14 Figure c shows the liquid phase mass spectra of the TC solution and the solution after 120 min degradation. By comparison, it can be found that the peak of the TC molecule (m / z=445) has completely disappeared after degradation, indicating that the TC molecule has been oxidized and reduced to other substances by the active groups. Finally, based on the above test results, three possible degradation pathways of TC molecules are inferred ( Fig.14Pathway I is that the TC molecule (m / z = 445) is attacked by ·OH radicals and then deamines to form T1 (m / z = 385), and then continues to demethylate to form T2 (m / z = 341), and then gradually forms T3 (m / z = 290) and T4 (m / z = 246) through a series of ring opening and molecular oxidation processes; in Pathway II, the TC molecule reacts with h + and O2 - The free radical reaction generates T5 (m / z=353), T6 (m / z=274) and T7 (m / z=230) through a series of demethylation, ring opening and dehydroxylation. For pathway III, the bond energy of the NC bond is low. - Under the attack of OH radicals, the amino group and methyl group will be removed to form T8 (m / z=417), which will be dehydrated to become T9 (m / z=362) intermediate, and then further demethylated and ring-opened under the attack of free radicals to become T10 (m / z=318) and T11 (m / z=262). As the photocatalytic oxidation progresses, the above intermediates are further transformed into substances with smaller molecular weights such as T12 (m / z=114), T13 (m / z=150) and T14 (m / z=218), and finally transformed into water and carbon dioxide.

[0107] Industrial wastewater in real life must contain various complex components, while the TC solution used in the above test is of high purity and does not contain other substances. Therefore, some common inorganic salt ions (NO3 - , Cl - 、SO4 2- 、Na + , Ca 2+ Mg 2+ and Fe 3+ ) to simulate real industrial wastewater to evaluate the photocatalytic activity of Bi2O3 / BNNS-3 in practical applications. 3+ In addition, other impurity ions only slightly inhibit the photocatalytic degradation of the material, which is presumably due to the competition between inorganic salt ions and TC molecules for limited active sites in the catalyst ( Fig.15 However, the overall removal effect of Bi2O3 / BNNS-3 on TC is still satisfactory. 3+ The addition of Bi2O3 / BNNS-3 caused the Fenton reaction to occur in the solution, so the degradation efficiency was slightly enhanced. In addition to TC, Bi2O3 / BNNS-3 also showed excellent photocatalytic degradation effects on OTC and DC ( Fig.15 In summary, the Bi2O3 / BNNS composite material has considerable photocatalytic degradation ability in practical applications.

[0108] The mechanism of photocatalytic degradation of TC molecules by the Bi2O3 / BNNS composite material of the present invention is as follows: Fig.16 ): The p-type semiconductor Bi2O3 and the n-type semiconductor BNNS are combined to form a pn junction. Due to the alignment of the Fermi levels of the two, their band structures have shifted to varying degrees, making the composite material have a more positive valence band and a more negative conduction band than Bi2O3 and BNNS, that is, the redox ability of the photogenerated electrons and holes is stronger. Under illumination, the photogenerated carriers inside the two materials are transferred under the action of the pn junction, where the photogenerated electrons in Bi2O3 are transferred to the surface of BNNS, and the photogenerated holes in BNNS are transferred to the surface of Bi2O3. This not only avoids the recombination of photogenerated carriers, but also generates a built-in electric field inside the catalyst, further increasing the carrier transfer rate. In addition, the photogenerated electrons and holes gather on the surfaces of BNNS and Bi2O3, respectively, so that their surfaces generate ·O2 - These free radicals then undergo redox reactions with TC molecules, ultimately degrading them into water, carbon dioxide, and other small molecules.

[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a pn-type Bi2O3 / BNNS heterojunction, characterized in that: Here are the steps: (1) Adding boric acid and urea to pure water, heating the mixture until the water evaporates, and then calcining I to obtain BNNS; (2) Bismuth nitrate pentahydrate is added to an N, N-dimethylformamide solution containing BNNS, and terephthalic acid is added to obtain a mixed solution I; the mixed solution I is subjected to a solvothermal reaction, and the obtained precipitate is washed, dried, and calcined to obtain a pn-type Bi2O3 / BNNS heterojunction.

2. The preparation method according to claim 1, characterized in that: The molar ratio of boric acid to urea in step (1) is 1:(6-48).

3. The preparation method according to claim 2, characterized in that: Calcination I in step (1) refers to calcination at 900-1100° C. for 2-4 h in nitrogen.

4. The preparation method according to claim 3, characterized in that: The mass ratio of bismuth nitrate pentahydrate, BNNS and terephthalic acid in the mixed solution I of step (2) is 1:(1.12-4.32):(0.06-0.35).

5. The preparation method according to claim 4, characterized in that: The temperature of the solvent thermal reaction in step (2) is 120-180° C. and the time is 9-15 h.

6. The preparation method according to claim 5, characterized in that: In the step (2), the temperature of calcination II is 180-220° C. and the time is 2-6 h.

7. A pn-type Bi2O3 / BNNS heterojunction prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the pn-type Bi2O3 / BNNS heterojunction according to claim 7 in photocatalytic degradation of antibiotics.

9. The use according to claim 8, characterized in that: The antibiotic is tetracycline, oxytetracycline hydrochloride or doxycycline hydrochloride.

10. The use according to claim 8, characterized in that: The steps of photocatalytic degradation of antibiotics are: adding a pn-type Bi2O3 / BNNS heterojunction to a solution containing antibiotics, first adsorbing it in a dark environment, and then placing it under a 300-420 nm wavelength, 300 W xenon lamp for photocatalytic degradation.

Citation Information

Patent Citations

  • Preparation method and application of BN / WO3 composite photocatalytic material

    CN104888835A

  • Sliding member and method for manufacturing sliding member

    CN116890099A

Cited By

  • Magnetic bismuth-based visible-light-driven photocatalyst as well as preparation method and application thereof

    CN120714634A